Resiliência e migração: um estudo sobre as crianças que retornaram do Japão - Sawaguchi, Glaucia Cristina Tiyomi (2013)
The present study had as an objective to comprehend how it is placed experience in migration process regarding Nikkei Brazilian children, who came from Japan by using as a reference the Jungian theoretical line. Such children, are Japanese descendent who spent the major part of its development in Japan and mandatorily have to fit into Brazil reality due to their parents current work. The subjects on the research are 46 children taking elementary school, participants at the Kaeru Project, both genders. As an instrument of research, it has been used the family drawing in movement, based on KFD (Kinetic Family Drawing) by Burns & Kaufman (1970), although varying through the performance of two drawings, one in Japan and another one in Brazil. Methodology used has been qualitative one, from established analysis category. Use of drawings has been useful in order to understand migration process once children involved in the research present difficult in expressing themselves orally due to a limited knowledge in both languages besides having to gather cultural content inherited by its ancestors. In addition to having verified adaptation success, it entails not only personal resources, but also relatives´ resources and society in which it´s inserted. As a result, it is possible to highlight that such children possess strong connection towards Japan, an appreciated country, although much idealized. They avoid demonstrating their intimacy and what they really feel, aspects also shown in Japanese cultural awareness. As part of a family system, results demonstrated a few individuals feeling excluded even from their family circle and it may take them, very frequently, to isolation